Lipschütz ulcer - Orozco-Sebá, Beatriz; Marchán-Cárdenas, Juan Camilo; Meléndez, Esperanza; Montagut, Alonso Joseph (Revista de la Asociación Colombiana de Dermatología y Cirugía Dermatológica, 2022)
Lipschütz ulcer is an entity of undetermined origin, characterized by the acute appearance of a vulvar ulcer, generally single, big-sized and with well-defined borders, in an adolescent or young woman without an active sexual life. Its diagnosis is usually a challenge for the health professional, since it is a rare and Little reported disease. It is diagnosed by dismissing other more common causes of vulvar ulcers, such as: venereal, systematic non-infectious, pharmacological, traumatic, or tumoral.